Efektivitas Ekstrak Biji Bintaro (Cerbera manghas) sebagai Larvasida Hayati pada Larva Aedes aegypti Instar III - Khoiriyanti Wulandari; Mei Ahyanti (Jurnal Kesehatan, 2018)
Dengue Hemorrhagic Fever (DHF) or Dengue Hemorrhagic Fever (DHF) is a disease caused by a virus which is very dangerous because it can cause the patient to die within a few days. Bandar Lampung city itself is a dengue endemic area. According to data from the Lampung Provincial Health Office, in 2015, from 15 there were 2,996 deaths in 31 people. The study aimed to knowing the effectiveness of bintaro seed extract (Cerbera manghas) as larvacide in III instars Aedes aegypti larvacides experimental research with post test only control group design. The sampling method was purposive sampling. Independent variables were bintaro seed extract (dose and time), the dependent variable was Aedes aegypti larvAedes The results showed that from 5 types of doses with 5 repetitions, the death result of Aedes aegypti larvae with a dose of 0% had no mortality, a dose of 0.1% with an average of 12.55, a dose of 0.5% with an average of 15.15 , 1% dose with an average of 18.20, a dose of 1.5% with an average of 22.15, and a dose of 2% with an average of 25. At the time of contact, the death result of the larvae was found with an average 6-hour contact time. an average of 8.70, 12 hours with an average of 14.13, 24 hours with an average of 18.37 and 48 hours with an average of 20.83. According to the results of statistical tests, the most effective effect of bintaro seed extract dosage is at a dose of 1.5% and contact time of 6 hours.